A Bibliometric Analysis of Current Research Trends in Korean Webtoons from 2018 to 2025 - Cahyo, Eko Nur; Darmanto, Darmanto; Muliawan , Anugrah Adi; Dewi , Ekka Zahra Puspita (Dinasti Research, 2025)
In the digital era, Webtoons have gained remarkable popularity, especially among young people accustomed to online media. This growth supports their global expansion as digital consumption rises. People increasingly prefer online entertainment, making Webtoons widely accessible. This paper is a quantitative research and is intended to examine keyword networks to analyze Webtoon-related studies. Results show “Webtoon” as the most frequent keyword, linked to themes such as Korean wave, brands, transmedia storytelling, and comics globalization. These connections highlight Webtoons’ transformation from digital comics into a global creative industry, influencing marketing, animation, and digital regulation. Although less frequent, transmedia storytelling remains significant, positioning Webtoons within a cross-media ecosystem adapted into films and dramas. Ultimately, Webtoons emerge as both cultural phenomena and creative industry drivers.